Legal Perspective on Copyright Controversy in the Song "Arjuna Looking for Love" - Salsabilasyah, Firyal Nur; Karren, Karren; Nadapdap, Cindy Debora Bestaida; Tarina, Dwi Desi Yayi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Copyright is one form of important aspect in the occurrence of material law in Indonesia. Legal protection of copyright in this context refers to efforts to protect the rights of creators from acts of infringement committed by irresponsible individuals. Legal protection efforts for song copyright in the Copyright Law consist of two forms, namely repressive and preventive protection. Repressive protection is a solution through a license agreement, while preventive protection is a solution through the application of criminal and civil sanctions against song copyright violators. Through this journal, we aim to educate about the importance of copyright protection and applicable and binding laws. This type of research uses normative juridical methods, in other words, researching with library materials or secondary data. Our group uses a legal approach and a conceptual approach. In the case of the song "Arjuna Looking for Love" by Dewa 19, there was an allegation of copyright infringement against Yudhistira Anm Massardi's work. After a legal debate, Dewa 19 decided to change the title of the song to "Arjuna" as a solution to the violation case. This case of plagiarism of Yudhistira's novel has been resolved in a non-litigation manner because it was resolved by simply changing the title of the song. The various challenges experienced in enforcing copyright emphasize us as a society regarding legal awareness as a very important effort in enforcing copyright.